CEK STABILITAS DAN PENGUKURAN LAJU KERMA UDARA. - Nur Asiah, Nurul Muthmainnah; Agus, jasdar (SAINFIS: Jurnal Sains Fisika, 2023)
Calibration is reasearch conducted to determine the correctness of the commendation of measuring instrument and measuring materials by comparison with traceable measuring standards to national and international standards for units of measurement or international standards and certified reference materials. In this activity, stability checks and air kerma were carried out using an 800cc detector using a Cs-137 radioactive source. A personal dosimeter is a device used to measure radiation dose cumulatively. The tools and materials used include detector 800cc, termaharobarometers, irradiators, cesium-137 radiation sources, lasers, steel rulers and compressors. CCTV monitor, Zero dosimeter, plaster and phantom. From the measurement activities that have been carried out, it is obtained that the value analyzed from the stability check carried out reads stable because it meets the set standard, namely % Deviation of 1%. So that when measuring air kerma a stable value is obtained, the farther the distance between the detector and the radiation source is, the lower the output value is read, the same goes for when using the Absorbed variation, the thicker the absorber used, the smaller the output value.Calibration is reasearch conducted to determine the correctness of the commendation of measuring instrument and measuring materials by comparison with traceable measuring standards to national and international standards for units of measurement or international standards and certified reference materials. In this activity, stability checks and air kerma were carried out using an 800cc detector using a Cs-137 radioactive source. A personal dosimeter is a device used to measure radiation dose cumulatively. The tools and materials used include detector 800cc, termaharobarometers, irradiators, cesium-137 radiation sources, lasers, steel rulers and compressors. CCTV monitor, Zero dosimeter, plaster and phantom. From the measurement activities that have been carried out, it is obtained that the value analyzed from the stability check carried out reads stable because it meets the set standard, namely % Deviation of 1%. So that when measuring air kerma a stable value is obtained, the farther the distance between the detector and the radiation source is, the lower the output value is read, the same goes for when using the Absorbed variation, the thicker the absorber used, the smaller the output value.